Representasi Pesan Moral Dalam Film ‘’jarak Antar Kanvas’’ (Analisis Semiotik Roland Barthes ) - Akmalia, Annisa; Octaviani, Vethy; Narti , Sri (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
In this very fast millennial era, it provides added value by easily accessing all information, also has an impact on people from various walks of life, especially teenagers today. This opportunity encourages teenagers to do something free to socialize. Promiscuity is now the influence of a teenager, where most teenagers today often abuse their lifestyle. This study aims to determine the Representation of Moral Messages in the Film ''Distance Between Canvases'' (Roland Barthes Semiotic Analysis). The collection of research data using observation techniques and documentation techniques is contained in the film in accordance with predetermined categorization. The results showed that there are 6 moral messages seen from the behavior style of today's adolescents, the first moral message, interactions between friendships that use abusive language such as calling 'dog' is one of the behavioral styles of today's adolescents that are considered normal by some people.Second, the moral ethics of the adolescent transitional association experience uncertainty and uncertainty and get a lot of temptation or attraction to do bad deeds. Third, the dating style of young people in this era legalizes immoral acts as a normal habit.Fourth, selective friendship with the quality of friendship is strongly influenced by personality in terms of the quality of friendship. The fifth moral is that regret and disappointment in a breakup results in regret and feeling aggrieved, one of which is due to infidelity. Sixth moral message true friends, every teenager wants a friendly relationship with quality. But sometimes teenagers do not realize if adolescents direct the problems experienced out of their identity.